Exercise Motivation Levels on Student Activity Unit (UKM Basketball) at Universitas Djuanda - Firdaus Hendry Prabowo Yudho; Aditia Nugroho (Inspiree)
The purpose of the study This study aims to determine how high the level of training motivation of athletes when carrying out training. The background of this research is the inconsistency level of achievement shown by the Basketball Student Activity Unit, Djuanda University, Bogor.